Laryngeal perforation during Sistrunk procedure. Issue 3 (22nd March 2021) - Matos, Leonor; Carvalho, Lúcia; Alves, Alexandre; Nora, Mário
Abstract: Thyroglossal duct cyst (TGDC) is the most common congenital neck anomaly in childhood, although it can be diagnosed at any age group. Ultrasound of the thyroid gland and the neck structures is an appropriate tool for diagnosis. The authors aim to report a rare case of a 22-year-old male with a laryngeal perforation during a TGDC excision and raise awareness to this potentially life-threatening complication. The Sistrunk procedure is the surgical treatment of choice with a low morbidity and recurrence rates.